Surface Geochemical Analysis on Outcrop Sample of Block PM322 Shoreline, Pantai Bagan Lalang / Nur Shuhadah Japperi … [et al.] - Japperi, Nur Shuhadah; Nik Ab Lah, Nik Khairul Irfan; Che Mohamed Hussein, Siti Nurliyana; Dollah, Aqilah; Othman, Nur Hidayati; Azman, Nur Bazilah (Faculty of Applied Sciences, 2019)
The use of surface geochemical exploration methods is based on the concept that all petroleum accumulations suffer some leakage to shallower intervals and eventually to the surface. The objective of this study is to analyze geochemical properties such as moisture content, grain size, and mineral properties of the outcrop sample. Subsequently to relate these geochemical properties with petroleum parameters such as porosity, permeability, fluid flow, type of rock, minerology, and chemical composition. Three samples were collected within 100m x 100m parameters to provide an average value result. The samples were taken 20cm below surface and on the shoreline of Pantai Bagan Lalang. The moisture content and organic content of the sample can be known as a percentage of its oven dried weight with its wet sample. The mechanical sieve method was conducted in accordance with ASTM D 422 for the grain size distribution analysis. Lastly, X-ray diffraction analysis was conducted to identify mineral composition based on the peak from a graphical result computed from the XRD machine. Water content analysis results was then related with the fluid flow of the samples while soil organic content was studied to identify shale deposition. Besides, grain size distribution analysis provided porosity range value and permeability overview when correlated with grain size and sorting of the samples. XRD analysis provided graphical data of mineral composition that can be correlated with sample history. In conclusion, Pantai Bagan Lalang indicates a negative quantitative value of a potential reservoir would have.